Recent progress in the two-photon fluorescent probes for metal ions - Juvekar, Vinayak; Park, Sang Jun; Yoon, Juyoung; Kim, Hwan Myung (Coordination Chemistry Reviews, 2021)
Two-photon microscopy (TPM) offers improved deep visualization of the target specimen with reduced phototoxicity, autofluorescence, and minimal light scattering. In combination with TPM, two-photon fluorescent probes enable the visualization of metal ion species distribution in live tissues. In this review, we have summarized the recent progress published between 2014 and 2020 in the development of two-photon probes for detecting metal ions in live cells and tissues. We began by describing designing strategies of two-photon probes for metal ion and brief history of two-photon metal ion visualization in live tissues. We then highlighted selected examples of two-photon probes that can detect alkali and alkali earth metals, and transition metals such as copper, zinc, iron ions, and other heavy metal ions as well.
Keywords: Metal ions; Tissue imaging; Two-photon microscopy; Two-photon probes